Psychosemantic Content of the Concept of Sexuality in the Language Consciousness of Adults - Андрій Шевцов; Вікторія Гупаловська (Психолінгвістика)
Introduction. The article presents the results of psycho-linguistic study of the representation in the linguistic consciousness, psychosemantic and psychological content of the relative neologism “sexuality” formed in the conditions of natural transcultural semiosis. Herein the author’s own definition of the phenomenon of sexuality was formulated.